The Colonial Politics of Hope critical junctures of indigenous-state relations - Lindroth, Marjo; Sinevaara-Niskanen, Heidi 1980- (Interventions, 2022)
"Through analyses of cases in Australia, Finland, Greenland and elsewhere, the book illuminates how states appropriate hope as a means to stall and circumscribe political processes of recognising the rights of indigenous peoples. The book examines hope in indigenous-state relations today. Engaging with hope both empirically and conceptually, the work analyses the dynamic between hope, politics and processes of rights and recognition. In particular, the book introduces the notion of the politics of hope and how it plays out in three salient cases: planned constitutional changes that would finally recognise the indigenous peoples of Australia, the lengthy debate on the ratification of ILO Convention 169 Concerning Indigenous and Tribal Peoples in Independent Countries in Finland and the prospect of Greenland's independence after its gaining self-government in 2009. Juxtaposing these contexts, the book illustrates the ways in which hope has become a useful political tool in enabling states to sidestep the peoples' claims for justice and redress. The book puts forward insights on the power of hope - by definition future oriented - in diminishing the urgency of present concerns. This is hope's most potent colonial force. This book brings together studies on indigenous-state relations, social scientific discussions on hope and critical post-colonial, feminist and governmentality analyses"--Provided by publisher.